The Influence of Organizational Culture, Work Environment on Employee Performance with Work Motivation as an Intervening Variable (Case Study: Online Retail XYZ Jakarta) - Syifaa Lathiifa; Chaerudin Chaerudin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyze the factors that affect employee performance at XYZ Jakarta Online Retail. The population of this study is all employees at XYZ Online Retail with a total sample of 134 employees with a period of semester 1 2020, semester 2 2020 and semester 1 2021. The endogenous variables used are work motivation and employee performance, while the exogenous variable used is organizational culture and organizational environment. The data analysis method used Structural Equation Model-Partial Least Square (SEM-PLS). The results of this study indicate that organizational culture has no effect on employee performance; organizational culture has a positive and significant effect on work motivation; work motivation has a positive and significant effect on employee performance; work environment has a positive and significant effect on work motivation; work environment has no effect on employee performance; work motivation is able to mediate organizational culture on employee performance; work motivation is also able to mediate the work environment on employee performance.